1996
DOI: 10.1177/0361198196154600117
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Accumulation and Pore Water Pressures at Base of Pavements

Abstract: A unique mechanism based on extensive field and laboratory studies is presented to account for certain premature failures of flexible pavements in cold areas like those in Scandinavia and in northern parts of Canada and the United States. Water condensing at the interface between pavement and granular base accumulates at subzero temperatures resulting in excess moisture in this zone. During the thaw period of the uppermost base layer, the excess water in the aggregate is trapped between impervious layers of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…As a matter of fact, water vapor flow can represent a major part of overall water flow especially in the case that temperature gradient is remarkable. The recent experimental evidences also proved that vapor flow in freezing soil could lead to large amount of ice formation, even dominate the moisture migration (Eigenbrod and Kennepohl, 1996;Guthrie et al, 2006;Wang et al, 2012). Additionally, water vapor flow significantly affects the movement of heat, since it drives a substantial amount of energy as the latent heat of vaporization (Sakai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, water vapor flow can represent a major part of overall water flow especially in the case that temperature gradient is remarkable. The recent experimental evidences also proved that vapor flow in freezing soil could lead to large amount of ice formation, even dominate the moisture migration (Eigenbrod and Kennepohl, 1996;Guthrie et al, 2006;Wang et al, 2012). Additionally, water vapor flow significantly affects the movement of heat, since it drives a substantial amount of energy as the latent heat of vaporization (Sakai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Morgenroth and Buchan (2009) found that the soil moisture differences are insignificant between pervious and impervious paving, while other studies have reported that soil moisture is generally greater in soil beneath paved rather than unpaved soil (Morgenroth et al, 2013;Qian et al, 2010). Some other researches have shown that soil moisture is not necessarily lower beneath impervious pavements (Eigenbrod and Kennepohl, 1996;Oh et al, 2010;Hedayati et al, 2014;Grabosky et al, 2009). Clearly more research is needed in this research field.…”
Section: Impervious Surfaces Caused Stress In Urban Plantsmentioning
confidence: 97%
“…The case reported by Li et al (2014) [1] refers to profile A 2 in Figure 1. Eigenbrod and Kennepohl (1996) [2] also reported that significant moisture accumulation due to vapour transfer occurred underneath a road pavement and led to significant frost heave damage to the pavement. As profile A 2 represents a deep groundwater table and a dry foundation soil, issues associated with high moisture content are more likely to be ignored in geotechnical design.…”
Section: Canopy Effect Under Impervious Coversmentioning
confidence: 99%
“…We first note that the two cases reported in the literature with significant moisture accumulation underneath impervious covers are both related to frozen soils (Li et al (2014) [1] ; Eigenbrod and Kennepohl (1996) [2] ). Another inspirational example is that ice tends to grow continuously inside an old type freezer (the non-frost-free type) as long as warm and humid air enters the freezer.…”
Section: A New Mechanism For Canopy Effectmentioning
confidence: 99%